Involvement of ClC-3 chloride/proton exchangers in controlling glutamatergic synaptic strength in cultured hippocampal neurons - Guzman, Raul E.; Alekov, Alexi K.; Filippov, Mikhail; Hegermann, Jan; Fahlke, Christoph (Frontiers in Cellular Neuroscience, 2014)
ClC-3 is a member of the CLC family of anion channels and transporters that localizes to early and late endosomes as well as to synaptic vesicles. Its genetic disruption in mouse models results in pronounced hippocampal and retinal neurodegeneration, suggesting that ClC-3 might be important for normal excitatory and/or inhibitory neurotransmission in central neurons. To characterize the role of ClC-3 in glutamate accumulation in synaptic vesicles we compared glutamatergic synaptic transmission in cultured hippocampal neurons from WT and Clcn3-/- mice. In Clcn3-/- neurons the amplitude and frequency of miniature as well as the amplitudes of action-potential evoked EPSCs were significantly increased as compared to WT neurons. The low-affinity competitive AMPA receptor antagonist -DGG reduced the quantal size of synaptic events more effectively in WT than in Clcn3-/- neurons, whereas no difference was observed for the high-affinity competitive non-NMDA antagonist NBQX. Paired pulse ratios of evoked EPSCs were significantly reduced, whereas the size of the readily releasable pool was not affected by the genetic ablation of ClC-3. Electron microscopy revealed increased volumes of synaptic vesicles in hippocampi of Clcn3-/- mice. Our findings demonstrate that ClC-3 controls fast excitatory synaptic transmission by regulating the amount of neurotransmitter as well as the release probability of synaptic vesicles. These results provide novel insights into the role of ClC-3 in synaptic transmission and identify excessive glutamate release as a likely basis of neurodegeneration in Clcn3-/-.